OVERVIEW OF PROCESS DETERMINATION AND POLICY IMPLEMENTATION OF OCCUPATIONAL SAFETY AND HEALTH MANAGEMENT SYSTEM AT A REGIONAL HOSPITAL IN SUMBAWA - Ardhianto Nugroho; Baju Widjasena; Bina Kurniawan (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Hospital occupational safety and health is a mandatory program for all hospitals in Indonesia, although, there all still several hospitals that dont have directed Hospital Occupational Safety and Health. A regional hospital in Sumbawa has problems like the lack of policy determination and the official written Hospital Occupational Safety and Health programs, some of the medical and non-medical personnels have not known the meaning and functions of Hospital Occupational Safety and Health, the deficiency of specific human resources on safety and health sectors, and the minimum support of funding and facilities for the implementation of Hospital Occupational Safety and Health. This research was done to know and understand the policy determination of Hospital Occupational Safety and Health Management System at a regional hospital in Sumbawa. This research was a qualitative and descriptive research. There were 5 main informants and 3 triangulations. The instruments of this research used profound interviewing guide and observation sheets. According to the Indonesian Ministry of Health Regulation number 66 of 2016 about Hospital Occupational Safety and Health, the researched hospital has generally met the requirements, but not all of the policies and purposes of the Hospital Occupational Safety and Health programs were well understood, supported, and applied by all of the stakeholders at the hospital, these were not in accordance with the qualification requirements and personnels competence in the Hospital Occupational Safety and Health organization. In addition, the policies and purposes also have not fulfilled the funding policies which was not 100% applied from the budget proposal, a specific funding for the Hospital Occupational Safety and Health was also not already proposed, and there was an uncertainty from the management about the funding and facilities which were not maximum.